ANALISIS HUBUNGAN PENGETAHUAN SIKAP IBU TERHADAP KUNJUNGAN ANTENATAL CARE DI PUSKESMAS - Safitry, Rusni; Firna, Fransiska; Haslan, Hasliana; Khair, Ummul; Hitipeuw, Anthoneta (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: ANC is the medical care of pregnant women performed by trained specialists in accordance with the criteria. The coverage of ANC visits by pregnant women to health workers is based on the Ministry of Health standard which has been set at a minimum of 6 times. Pregnant women at Puskesmas Mijen II Demak Regency do not regularly perform ANC and respondents know that ANC visits during pregnancy are important but are not carried out regularly and reasoned lazy, work, no complaints, and lack of economy. The purpose of the study was to determine the relationship between knowledge and attitudes of pregnant women about ANC with ANC visits at the Mijen II Health Center, Demak Regency. The type of research used was quantitative analytic design with a cross sectional approach. The sample in the study was 39 respondents through purposive sampling technique. Chi Square test was used as data analysis in the study. The results showed there was no relationship between knowledge (p value: 0.176) and attitudes of pregnant women (p value: 0.060) towards ANC visits. It is recommended for pregnant women to conduct ANC visits according to the KEMENKES standard recommendations at least 6 times, namely 2 times at the doctor and 4 times at the midwife to prevent and find out the occurrence of complications early so that it can reduce AKI and AKB in Indonesia.Keywords: ANC, Knowledge, Attitude